(untitled) (The Pakistan Development Review, 2013)
This study intends to ascertain the impact of socio-economic, demographic and deterrent variables and the effect of technical criminal know-how and past criminal experience on property crime rate. The property crime equation comprises of the following independent variables: population density, unemployment rate, literacy rate, police strength and number of police proclaimed offenders in a society. The property crime equation has been estimated by using a time-series data set for Punjab from 1978 to 2012. We have applied Johansen cointegration approach to test the long run relationship among the variables. Empirical findings suggest that police strength has a deterrent effect while past criminal experience enhances property crime rate in Punjab. The study finds population density has a significant positive relationship while education has a significant negative relationship with property crime rate. Further we also find a negative relationship between unemployment and property crime which is supported by the concept of ‘consensus of doubt’ in the discipline of crime and economics. JEL Classification: D6